An organizational digital footprint for interruption management: a data-driven approach. Issue 8 (23rd November 2022) - Kalliomäki-Levanto, Tiina; Ukkonen, Antti
Abstract : Purpose: Interruptions are prevalent in knowledge work, and their negative consequences have driven research to find ways for interruption management. However, these means almost always leave the responsibility and burden of interruptions with individual knowledge workers. System-level approaches for interruption management, on the other hand, have the potential to reduce the burden on employees. This paper's objective is to pave way for system-level interruption management by showing that data about factual characteristics of work can be used to identify interrupting situations. Design/methodology/approach: The authors provide a demonstration of using trace data from information and communications technology (ICT)-systems and machine learning to identify interrupting situations. They conduct a "simulation" of automated data collection by asking employees of two companies to provide information concerning situations and interruptions through weekly reports. They obtain information regarding four organizational elements: task, people, technology and structure, and employ classification trees to show that this data can be used to identify situations across which the level of interruptions differs. Findings: The authors show that it is possible to identifying interrupting situations from trace data. During the eight-week observation period in Company A they identified seven and in Company B four different situations each having a different probability of occurrence of interruptions. Originality/value: The authors extend employee-level interruption management to the system-level by using "task" as a bridging concept. Task is a core concept in both traditional interruption research and Leavitt's 1965 socio-technical model which allows us to connect other organizational elements (people, structure and technology) to interruptions.